Diagnostic utility of additional conventional techniques after endobronchial ultrasonography guidance during transbronchial biopsy. Issue 6 (1st June 2016) - Kunimasa, Kei; Tachihara, Motoko; Tamura, Daisuke; Tokunaga, Shuntaro; Nakata, Kyosuke; Hazeki, Nobuko; Kamiryo, Hiroshi; Kobayashi, Kazuyuki; Sakai, Yasuhiro; Nishimura, Yoshihiro
Abstract: Background and objective: Endobronchial ultrasonography with a guide sheath transbronchial biopsy (EBUS‐GS TBB) has been used to diagnose peripheral pulmonary lesions (PPLs). In this study, we evaluated the diagnostic utility of conventional TBB after EBUS‐GS TBB. Methods: A retrospective analysis of patients who underwent conventional TBB after EBUS‐GS TBB for PPL between August 1, 2012 and December 31, 2014. We performed multivariate analysis to examine the association of various clinical factors, including EBUS probe distance and sample size area, with diagnostic yield. Results: Of 88 eligible patients, 57 (65%) were successfully diagnosed by EBUS‐GS TBB. In 31 patients not diagnosed by EBUS‐GS TBB, 15 (48%) were successfully diagnosed by additional conventional TBB. Ground glass opacity (GGO) was a significant factor associated with the diagnostic yield of additional conventional TBB following EBUS‐GS TBB. Multivariate analysis and receiver operator curves revealed that distance between the PPL and the EBUS probe of less than 2.55 mm favored the utility of conventional TBB. Conclusion: Additional conventional TBB after EBUS‐GS TBB could be a useful procedure for the diagnosis of ground glass opacity PPLs and in cases of a distance of less than 2.55 mm between the EBUS probe and the lesion. Abstract : Our study shows that additional conventional transbronchial biopsy after endobronchial ultrasonography with a guide sheath could be useful for the diagnosis of ground glass opacity––peripheral pulmonary lesions and in cases were the distance of the endobronchial ultrasonography probe to the lesion is shorter than 2.55 mm.